Analysis Of Factors Influencing Souvenir Buying Decisions (Study On Gmmtv Fans In Jabodetabek) - Syahidah, Hanna Asma; Nurmahdi, Adi (Journal of Social Research, 2023)
The purpose of this study is to determine and assess the impact of fan loyalty and price perceptions on the decision to purchase GMMTV souvenirs, with product placement serving as a moderating variable. The subjects of this study were Jabodetabek fans who had purchased souvenirs. The sample size in this study was determined using Hair's formula, resulting in a sample size of 120 participants. This study was carried out by delivering questionnaires to 141 respondents. The research hypothesis was tested using SmartPLS 4.0 software and a Partial Least Square (PLS) based Structural Equation Model (SEM). The variables that are examined in this study are fan loyalty, price perceptions, product placement, and purchasing decisions. In this study, data were tested using the Measurement Model Test (Outer Model) and the Structural Model Test (Inner Model). According to the findings, customer purchasing decisions for GMMTV souvenirs are influenced by the variables of fan loyalty, price perception, and product placement individually. The results for each fan loyalty and price perception variable, however, varied when the relationship between fan loyalty and price perception was tested using the mediating variable of product placement. Price perception has a considerable influence on purchase decisions when mediated by the product placement variable, as evidenced by a t-statistic value of 2.006 and a p-value of 0.045. Price perception has a considerable influence on purchase decisions when mediated by the product placement variable, as evidenced by a t-statistic value of 2.006 and a p-value of 0.045. Meanwhile, with a t-statistic of 1.410 and a p-value of 0.159, the fan loyalty variable mediated by product placement on purchase decisions has no effect, and the hypothesis is rejected.